Global impact of COVID-19 on newborn screening programmes - Koracin, Vanesa (BMJ Publishing Group, 2022)
Introduction The global COVID-19 pandemic has presented extraordinary disruption to healthcare services and exposed them to numerous challenges. Newborn screening (NBS) programmes were also affected; however, scarce data exist on the impact of COVID-19 on NBS. Methods We conducted an international survey to assess the global impact of COVID-19 on NBS, with the main aim of gathering the experiences of the COVID-19 pandemic from a large and representative number of NBS centres worldwide. Results The results of our study showed that COVID-19 impacted the NBS programmes, at least partially, in 29 out of 38 responding countries. Majority of the screening centres experienced a broad spectrum of difficulties and most were affected more in the second wave of the pandemic. Delays and unreliability with the postal service as well as flight cancellations caused delays in samples arriving to screening centres and with the provision of laboratory equipment and reagents. The availability of laboratory staff was sometimes reduced due to infection, quarantine or reassignment within the healthcare facility. Sample collection at home, second-tier tests and follow-up were also affected. Social restrictions and interruptions in public transport added to these difficulties. Only a limited number of centres managed to retain a fully functioning NBS programme. Conclusion As the pandemic might continue or could recur in future years, it would be useful to develop guidelines to protect these valuable services.